2011
DOI: 10.1080/13854046.2011.566892
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Complaints Following Reports of Blast Versus Non-Blast Mild TBI: Does Mechanism of Injury Matter?

Abstract: Patients with a reported history of mild traumatic brain injury (mild TBI) due to blast (n = 298) or non-blast (n = 92) mechanisms were asked to complete the Neurobehavioral Symptom Inventory (NSI) and the Post-traumatic Stress Disorder Checklist (PCL). Mechanism of injury did not account for a significant amount of variance in post-concussion symptom reporting overall, nor did severity of mild TBI (i.e., brief loss of consciousness versus only an alteration of consciousness). Symptom reporting was greater in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 44 publications
3
95
1
Order By: Relevance
“…29,30,53,54 Tinnitus was associated with TBI characteristics. Consistent with prior cross-sectional studies showing higher rates of tinnitus 20 and hearing problems 28 following blast versus nonblast injuries, postdeployment tinnitus was nearly twice as likely for those with nonblast TBI and nearly 3 times as likely for those with blast TBI compared with those with no TBI. In addition, tinnitus was 1.8 times as likely after a single TBI and 2.3 times as likely after multiple TBIs compared with tinnitus occurrence in those with no TBI.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…29,30,53,54 Tinnitus was associated with TBI characteristics. Consistent with prior cross-sectional studies showing higher rates of tinnitus 20 and hearing problems 28 following blast versus nonblast injuries, postdeployment tinnitus was nearly twice as likely for those with nonblast TBI and nearly 3 times as likely for those with blast TBI compared with those with no TBI. In addition, tinnitus was 1.8 times as likely after a single TBI and 2.3 times as likely after multiple TBIs compared with tinnitus occurrence in those with no TBI.…”
Section: Discussionsupporting
confidence: 77%
“…25 This shearing force directly injures the brain and cochlea, causing an inflammatory response, oxidative stress-induced neural degeneration, 26 and subsequent neural alteration both within the cochlea and its auditory pathway. 27 Establishing a direct, causal link between blast exposure and tinnitus has been limited by the retrospective, cross-sectional nature of available accounts [28][29][30] and the existence of comorbid psychiatric disorders such as posttraumatic stress disorder (PTSD). 31,32 Failure to differentiate tinnitus symptoms from these comorbidities further hinders the identification of tinnitus-specific treatment modalities.…”
mentioning
confidence: 99%
“…For the milTBI group, five participants (24% of the sample) had been exposed to a single blast event, 8 (38%) reported two blast exposures, and the remaining eight (38%) reported multiple blast exposures (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For the civTBI group, six (29%) participants had a history of a single concussion, five (24%) reported two concussions, and eight (38%) reported multiple concussions (range 3-10; data on additional concussions were not available for two participants in this group).…”
Section: Resultsmentioning
confidence: 99%
“…Although we have observed subtle differences in cognitive performance in blast-related TBI, 19 the cognitive deficits observed in the acute and subacute stage of mild to moderate TBI typically resolve in the chronic stage. Belanger and associates 20 have suggested that any differences between blast-related and mechanical TBI are likely the result of increased levels of psychological distress in blast-related TBI rather than any unique differences in brain pathology. An alternative strategy for differentiating blast-related from mechanical TBI is to identify unique neural signatures in brain activation patterns using functional magnetic resonance imaging (fMRI).…”
Section: T Raumatic Brain Injury (Tbi) Is Common In Military Personnementioning
confidence: 99%
“…Some authors have concluded that these auditory complaints reflect symptoms primarily associated with posttraumatic stress disorder (PTSD) [15], while others suggest they are associated with blastrelated TBI [16], and more specifically, blast-related damage to the central auditory system [11][12][17][18]. The proposed mechanism for such damage is that a primary blast injury leads to contusions from the brain moving within skull, hemorrhaging from the tearing of surface veins, and diffuse axonal injury as neurons are sheared and stretched in the lower-and mid-brainstem nuclei, thalamus, and corpus callosum and synaptic structures connecting nuclei within the central auditory system [6,[19][20], which in turn negatively affects auditory and speech processing [18].…”
Section: Introductionmentioning
confidence: 99%